Transgenerational sex determination: the embryonic environment experienced by a male affects offspring sex ratio - Warner, Daniel A. (Nature Publishing Group, 2013)
Conditions experienced during embryonic development can have lasting effects, even carrying across generations. Most evidence for transgenerational effects comes from studies of female mammals, with much less known about egg-laying organisms or paternally-mediated effects. Here we show that offspring sex can be affected by the incubation temperature its father experiences years earlier. We incubated eggs of an Australian lizard with temperature-dependent sex determination under three thermal regimes; some eggs were given an aromatase inhibitor to produce sons at temperatures that usually produce only daughters. Offspring were raised to maturity and freely interbred within field enclosures. After incubating eggs of the subsequent generation and assigning parentage, we found that the developmental temperature experienced by a male significantly influences the sex of his future progeny. This transgenerational effect on sex ratio may reflect an epigenetic influence on paternally-inherited DNA. Clearly, sex determination in reptiles is far more complex than is currently envisaged.